Assay Of Clopidogrel By Visible Spectrophotometry - B.ANUPAMA; V.JAGATHI; A.APARNA; M.MADHUBABU; V.LAKSHMI ANNAPURNA (International Journal of Pharma and Bio Sciences, 2011)
Three simple and sensitive spectrophotometric methods have been developed for the estimation of Clopidogrel (CLP) in pure and pharmaceutical dosage forms. This method is based on the formation of ion-pair complexes of the drug with acidic dye Solochrome black T (SBT : λmax 510 nm) , This method is based on Oxidation of the drug with Phenanthroline (Fe(III)/PTL: λmax 515 nm) and This method is based on oxidation followed by complex formation when the drug reacts with potassium permanganate (KMnO4 λmax 410nm). These methods have been statistically evaluated and found to be precise and accurate.